If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + 5) + -6 = 3(3 + w) Reorder the terms: 3(5 + w) + -6 = 3(3 + w) (5 * 3 + w * 3) + -6 = 3(3 + w) (15 + 3w) + -6 = 3(3 + w) Reorder the terms: 15 + -6 + 3w = 3(3 + w) Combine like terms: 15 + -6 = 9 9 + 3w = 3(3 + w) 9 + 3w = (3 * 3 + w * 3) 9 + 3w = (9 + 3w) Add '-9' to each side of the equation. 9 + -9 + 3w = 9 + -9 + 3w Combine like terms: 9 + -9 = 0 0 + 3w = 9 + -9 + 3w 3w = 9 + -9 + 3w Combine like terms: 9 + -9 = 0 3w = 0 + 3w 3w = 3w Add '-3w' to each side of the equation. 3w + -3w = 3w + -3w Combine like terms: 3w + -3w = 0 0 = 3w + -3w Combine like terms: 3w + -3w = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| n+(-83)=-124 | | 7x-4=-48-4x | | 10x-13=37+20x^2 | | 2x+9=33+6x | | 2x^2+16x=-3 | | -7x=-5x+24 | | x-8.7=-6.7 | | (x^3-6x^2+9x-4)=0 | | (r+7)(r-18)=0 | | 0.7n+5.4=-1*3/5 | | -7x-4=122+7x | | 3(z-5)+17=-4 | | (8x-3)(x^2-4)=0 | | 5x-4x=30 | | z+36=13 | | -s+s/4+5=14 | | 7000t=63.5t | | 6x+1=9-10x | | 4n+(-2)=n+8 | | 14/5+6/5= | | n/3+1*1/3=4 | | -7x-2=5x+16 | | 4x-(3x+4)=1 | | 4x-5=7-2 | | 4t-8=32+9t | | 6(3.2z-1)=3.6 | | -7x-2=-5+16 | | 2x=4.88 | | n/3+11/3=4 | | 8f-(-3)=6 | | 2x=14.88 | | u=w+z |